Coopetition and convergence in the ICT ecosystem. Issue 7 (August 2015) - Basole, Rahul C.; Park, Hyunwoo; Barnett, Brandon C.
Abstract: This study focuses on quantifying and visualizing the competitive dynamics shaping the ICT ecosystem. We ground our study in theories of complex systems, strategy dynamics, and industry life cycle. Using a unique longitudinal dataset, we define and develop graph and information theoretic measures of coopetition, convergence, complexity, and velocity of the ICT ecosystem. We frame the "transformation path" of the ICT ecosystem using these proposed metrics and map the trajectory using complex network visualizations. Our results show that while segments in the ICT ecosystem have converged, the rate of convergence is decreasing. This suggests a growing maturity of the ecosystem and decreasing importance on formal interfirm relationships. At the same time, we find that coopetition is increasing at a decreasing rate. We also find evidence of a declining engagement in interfirm R&D and a growing number of technology transfer relationships, indicating a possible shift from value exploration to value capturing. Our novel data-based metrics provide a foundation for strategic analysis of new business opportunities that is not possible using traditional market analysis tools. We conclude with a discussion of policy implications and future research opportunities. Abstract : Highlights: Quantify coopetition, convergence, complexity, and velocity of the ICT ecosystem. Visualize transformation path of the ecosystem in the underlying opportunity space. Provide decision makers with insights about patterns of ecosystem evolution. Develop novel foundation for strategic analysis of business opportunities.